Our Kids: The American Dream in Crisis - Robert D. Putnam (Simon & Schuster; Reprint edition, 2016)
Central to the very idea of America is the principle that we are a nation of opportunity. But over the last quarter century we have seen a disturbing â€œopportunity gapâ€ emerge. We Americans have always believed that those who have talent and try hard will succeed, but this central tenet of the American Dream seems no longer true or at the least, much less true than it was.